CONCEPTUALIZATION OF PSYCHOLOGICAL FIRST AID AND ITS IMPLICATION TO NURSING - Dr. Suresh Patil; Dr. Tanveer Ahmed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2024)
The necessity for psychological first aid (PFA) in crisis response and developmental initiatives has been increasingly evident in recent years, as the nation experiences several emergencies, natural catastrophes, and pandemics such as COVID-19. Health services are among the most commonly sought services during catastrophes, and there is an expectation for high quality provision. Preparedness for calamities is an essential imperative. Psychological first aid is the preferred acute intervention for addressing the psychological needs of children, adults, and families impacted by disasters and pandemics. The most effective method to conceptualise PFA is as the psychological equivalent of physical first aid.